Toy story (Grolier New York, 1996)
Join Woody and Buzz Lightyear for their first adventure! Woody the cowboy is Andy$1 (Bs favorite toy. But when a high-tech newcomer named Buzz Lightyear becomes Andy$1 (Bs new favorite, Woody and Buzz will end up on an adventure like no other!s